2015
DOI: 10.1002/anie.201502075
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(0)/PAr3‐Catalyzed Intermolecular Amination of C(sp3)H Bonds: Synthesis of β‐Amino Acids

Abstract: An intermolecular C(sp(3))-H amination using a Pd(0) /PAr3 catalyst was developed. The reaction begins with oxidative addition of R2 N-OBz to a Pd(0) /PAr3 catalyst and subsequent cleavage of a C(sp(3))-H bond by the generated Pd-NR2 intermediate. The catalytic cycle proceeds without the need for external oxidants in a similar manner to the extensively studied palladium(0)-catalyzed C-H arylation reactions. The electron-deficient triarylphosphine ligand is crucial for this C(sp(3))-H amination reaction to occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(55 citation statements)
references
References 55 publications
1
52
0
2
Order By: Relevance
“…Based on our previous work concerning ortho -C–H amination using O -benzoyl hydroxylmorpholine as the aminating reagent, 12 we found that reaction of 1a with this aminating reagent in the presence of 10 mol% Pd(OAc) 2 , 20 mol% 3-acetylamino-2-hydroxy pyridine ligand ( L1 ), K 3 PO 4 (3.0 equiv.) and AgOAc (3.0 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous work concerning ortho -C–H amination using O -benzoyl hydroxylmorpholine as the aminating reagent, 12 we found that reaction of 1a with this aminating reagent in the presence of 10 mol% Pd(OAc) 2 , 20 mol% 3-acetylamino-2-hydroxy pyridine ligand ( L1 ), K 3 PO 4 (3.0 equiv.) and AgOAc (3.0 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…Amination of C(sp 2 )−H bonds by alkylamines was recently reported by Daugulis (Scheme a) . Due to lack of π‐bond coordinating character, C(sp 3 )−H activation for C(sp 3 )−N bond formation is challenging, and limited examples have been developed until now, exemplified by C(sp 3 )−H amidation by Che and C(sp 3 )−H aminations by Yu and Qin by using benzoyloxyamines as aminating reagents (Scheme b,c). Direct amination of unactivated C(sp 3 )−H bonds by alkylamines to construct C(sp 3 )−N bonds represents an unmet challenge and has never been reported, but offers a great advantage in that it saves extra steps for the preparation of benzoyloxyamines and simplifies the overall synthetic procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Mit dem Hydroxylamin 139 als elektrophiler Stickstoffquelle liefert die intermolekulare C-H-Aminierung des Amids 138 das aminierte Produkt 140. [64] Wenn das Palladiumalkyl-Intermediat mit Selectfluor (141)a bgefangen wird, kann ein Fluoratom an der C-H-Bindung des Amids 127 eingebaut werden. [65] Mit B 2 pin 2 kann eine Borylierung vollzogen werden, wodurch das Amid 144 gebildet wird.…”
Section: Amine (Sulfonamide)unclassified